Men’s Perceptions and Emotional Responses to Becoming a Caregiver Father: The Role of Individual Differences in Masculine Honor Ideals and Reputation Concerns - Gul, Pelin; Uskul, Ayse K. (Frontiers in Psychology, 2019)
Despite the rising number of men and women in counter-stereotypical roles, it is rare for men to serve as primary caregivers in families with dependent children. In two studies, we examined how British men and women perceive and emotionally react to primary caregiver (vs. breadwinner) fathers, whether their perceptions and reactions are contingent upon individual differences in masculine honor endorsement, and the potential mediators in these relationships. Results showed that both men and women perceived the primary caregiver fathers more positively – warmer and not less competent – than the primary breadwinner fathers, yet endorsement of masculine honor ideals increased men’s (but not women’s) tendency to attribute less positive emotions (e.g., proud and satisfied) and more negative emotions (e.g., ashamed and resentful) to the primary caregiver (vs. breadwinner) fathers. Mediated moderation analyses showed that for men with high masculine honor orientation, their less positive and more negative emotional attributions were driven by perceived loss of reputation among male friends, whereas for men with low masculine honor orientation, their more positive and less negative emotional attributions were driven by perceived gain of wife’s and children’s admiration. By shifting the focus to men’s individual differences and motives, these findings offer nuanced explanations for why some men may feel eager about serving as caregiver fathers, whereas others may feel reluctant to do so.